Non-adiabatic effects in the H3+ spectrum. (23rd September 2019) - Amaral, Paulo H. R.; Stanke, Monika; Adamowicz, Ludwik; Diniz, Leonardo G.; Mohallem, José R.; Alijah, Alexander
Abstract : The effect of non-adiabatic coupling on the computed rovibrational energy levels amounts to about 2 cm −1 for H3 + and must be included in high-accuracy calculations. Different strategies to obtain the corresponding energy shifts are reviewed in the article. A promising way is to introduce effective vibrational reduced masses that depend on the nuclear configuration. A new empirical method that uses the stockholder atoms-in-molecules approach to this effect is presented and applied to H3 + . Furthermore, a highly accurate potential energy surface for the D3 + isotopologue, which includes relativistic and leading quantum electrodynamic terms, is constructed and used to analyse the observed rovibrational frequencies for this molecule. Accurate band origins are obtained that improve existing data. This article is part of a discussion meeting issue 'Advances in hydrogen molecular ions: H3 +, H5 + and beyond'.